Comparing clinical characteristics of pediatric patients with pancreatic diabetes to patients with type 1 diabetes: a matched case-control study - Lanzinger, Stefanie; Grulich-Henn, Jürgen (Pediatric diabetes, 2019)
Background Only few studies have been conducted on pancreatic diabetes and data from large epidemiological studies are missing. Our main objective was to study the most important differences and similarities between pediatric individuals with pancreatic diabetes and type 1 diabetes (T1D). Methods Patients <20 years of age were identified from the diabetes patient follow-up registry (DPV). Data of the most recent treatment year between January 2000 and March 2018 were aggregated. Propensity score was used to match individuals with pancreatic diabetes to individuals with T1D. Matching was conducted one-to-one by sex, age, diabetes duration, body mass index SD score (BMI-SDS), and migration background. Results We studied 731 individuals with pancreatic diabetes and 74 460 with T1D. In the matched cohort of 631 pairs, HbA1c was significantly lower in pancreatic diabetes (7.4% [95% confidence interval: 7.2; 7.5%]) compared to T1D patients (8.7% [8.5; 8.8%]). Daily insulin dose (0.80 IU/kg [0.77; 0.84] vs 0.86 IU/kg [0.82; 0.90]) and insulin pump use (13.3% [10.7; 16.4] vs 22.1% [19.0; 25.6%]) were lower in patients with pancreatic diabetes. However, event rates of severe hypoglycemia were similar between pancreatic and T1D patients (8.8 [5.4; 14.2] vs 9.6 [5.9; 15.6] events per 100 patient years). Conclusions With the use of robust epidemiological data, our study improves the knowledge on clinical characteristics in pediatric individuals with pancreatic diabetes. Moreover, our results serve as a basis to reconsider treatment options and for discussing clinical practice guidelines for patients with this rare medical condition.
Gesehen am 05.11.2019